Employee Communication and Participation Practices in Nepalese State-owned Banks under Restructuring Program - Chapagai, Rishi Ram (PYC Nepal Journal of Management, 2012)
This article examines general of employee communication and participation practices under the restructuring program of the two state-owned commercial banks of Nepal which are chosen for this study. Descriptive research design was used for the study. The study conducted a questionnaire survey of 105 managerial level employees; of which 67(63.81 percent) questionnaires were received in usable form. Descriptive statistical tools were applied for the analysis of the data. The findings reveal that the state-owned banks improved communication through the use of workplace newsletters, official website and e-mail. Findings of the study also show that the information about the internal investment plans, HR planning, financial position of the organization, technological change, and restructuring and redundancies programme are communicated to employees. Similarly, employee participation also seed improved under the restructuring program of the bank. The study also evidences that employees’ representatives participate in meeting with senior managers to discuss on core service issues, employment issues, financial issues, future plans and other organizational organization issues.